Management skills in schools : a resource for school leaders - Jones, Jeff, 1950- (Paul Chapman, 2004)
"For the discerning leader wanting to develop their personal management skills this is a 'must have' resource"--Coleen R Jackson, Director, Roehampton Education Leadership Centre, University of Surrey Roehampton. In this book, Jeff Jones shows how managers in education can contribute to school improvement, and focuses on the essential personal and practical management skills needed to instil a positive team culture and support colleagues effectively